A socio-technical lens on security in sustainability transitions: Future expectations for positive and negative security. (August 2022) - Kivimaa, Paula; Brisbois, Marie Claire; Jayaram, Dhanasree; Hakala, Emma; Siddi, Marco
Abstract: A transition to net-zero carbon energy systems, imperative to combat climate change, is unfolding around the world. Other socio-technical systems also face the need to transition to become more environmentally and socially sustainable. We argue that such transitions will have both positive and negative security implications on numerous issues which deserve attention but have been little addressed in transition studies. We take a socio-technical lens and propose that these security implications can be ex-ante analysed via three elements of socio-technical systems: technology, actors, and institutions. We provide an illustration of such analysis in the energy transition context and use this to create a categorisation framework for expectations analysis. Regarding the technology dimension, expectations concerning, e.g., resource and technology dependencies, risk for technical system disruptions, and effects on interconnected systems can be analysed as relevant security issues. For the actor dimension, issues such as geopolitical uncertainties, regional (in)stability, internal tensions, and diffusion of power are identified. For institutions, e.g., influence on democratic institutions, peace building and structural violence can be assessed. We argue there is a need for improved and forward-looking policy coordination across domains and for academic studies that utilise foresight approaches to assess different security expectations more concretely. Highlights: Combines a socio-technical lens with security studies for expectations analysis. Addresses positive and negative security via technology, actors and institutions. Technological risks include new dependencies on critical materials and cyber security. Shows tensions and opportunities for peace building and energy justice. Sustainability transitions impact military institutions and employment structures.